Identification and characterization of a cathepsin L-like cysteine protease from Gnathostoma spinigerum - Natthawan Kongkerd (2018)
Gnathostoma spinigerum is a causative agent of human gnathostomiasis, a common parasitic disease involving skin and visceral organs, especially the central nervous system. In this study, we identified a cDNA encoding a cathepsin L-like cysteine protease (GsCL1) from the λZAP cDNA library of G. spinigerum advanced third-stage larva (aL3) and characterized the biochemical properties of the recombinant enzyme. The cloned cDNA of 1484 bp encoded 398 amino acids which contained a typical signal peptide sequence (23 amino acids), a pro-domain (156 amino acids), and a mature domain (219 amino acids) with an approximate molecular weight of 24 kDa. The deduced amino acid sequence of GsCL1 gene showed 53-64% identity to cathepsin L proteases of various organisms including a cathepsin L family member (cpl-1) of Caenorhabditis elegans. Recombinant proGsCL1 expressed in Pichia pastoris showed typical biochemical characteristics of cysteine proteases. The expressed enzyme displayed optimal protease activity toward Z-Phe-Arg-AMC substrate at pH 6.0 but not toward Z-Arg-Arg-AMC. The activity was sensitive to cysteine protease inhibitors E-64 and K11777. The preference for large hydrophilic and aromatic residues in the P2 position (I, L, F, W, U, V) was typical of cathepsin L proteases. Mouse anti-GST-proGsCL1 serum showed reactivity with 35-, 38- and 45-kDa proteins in the aL3 extracts. These proteins were shown to localize inside the intestinal cells of aL3. © 2008 Elsevier B.V.